E-Government in Malaysia: E-services implementation / Filzaizzati Aliatie Ali and Nurfatin Mohammed Yunus - Ali, Filzaizzati Aliatie; Mohammed Yunus, Nurfatin (2015)
The growth of ICT made government transform their communication with citizens in order to improve public expectation and demands for increased and quality services, thus ICT aims is to speed and ease in service provision (Noore, 2005). Hence, government over the world is under pressure to make their services available via internet (Chang, 2006). E-Government is a short term of electronic government, where administration will adopt e-Government to enhance their services delivery for public. e-Government gives new style of living for people globally, where everything will be easy and fast, under e-Government there is initiative that being provided by government called e-Services where citizens does not have to go the counter to get government services such as bill payment, and citizens can access government inforation for 24 hours and 7 days a week through electronic devices. Thus, focus on e-Service which under e-Government project, it is in line with paperless concept to reduce paper used for supporting green environment. By implementing e-Services, many benefits being highlighted such as high efficiency, transparency, and accountability of the government. e-Service also used non-internet procedures include Personal Digital Assistant (PDA), Short Message Service (SMS), Fax and television for deliver any information from government to public (M.Syukri and Patmawatie, 2013).